Implementasi Model Problem Based Instruction terhadap Penguasaan Materi Hukum Newton dan Kecakapan Berpikir Kritis Siswa - Umayya Ulfa; Anggu Winata (SPEJ (Science and Physic Education Journal), 2021)
This study aims to determine the difference in the achievement of students' average scores between the implementation of the problem based instruction (PBI) model and conventional learning on student activities, mastery of Newton's Law material, and students' critical thinking skills. This research method is a true experiment using a randomized control-group pre-test-post-test design, where the experimental class and the control class are given pre-test and post-test. The results of this study indicate, a) in the psychomotor aspect, the percentage of the good category for the experimental class is on average higher than the control class, while in the affective aspect there is no significant difference; b) there is a significant difference in the mastery of Newton's Law material between students taught through the implementation of the PBI model with an average change in value of 56.59 compared to conventional learning of 46.14; c) there is a significant difference in critical thinking skills between students taught through the implementation of the PBI model with an average change in score of 55.85 compared to conventional learning of 45.62. The conclusion, that the implementation of PBI the average score of psychomotor activity, mastery of Newton's Law material, and students' critical thinking skills are significantly different compared to conventional learning. Keywords: Critical Thinking Skills, Newton's Law Material, Problem Based Instruction Model, Conventional Learning